2015
DOI: 10.4244/eijy14m07_02
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of contrast medium induced Pd/Pa ratio in predicting functional significance of intermediate coronary artery stenosis assessed by fractional flow reserve: insights from the RINASCI study

Abstract: CMR is accurate in predicting the functional significance of coronary stenosis. This could allow limiting the use of adenosine to obtain FFR to doubtful cases. In particular, we suggest considering a CMR value ≤0.83 to be significant, a CMR value ≥0.88 as not significant, and inducing maximal hyperaemia using adenosine for FFR assessment when CMR is between 0.84 and 0.87.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…5 However, adenosine can be contraindicated in some patients with asthma or severe chronic obstructive pulmonary disease (COPD), it can induce conductive complications (transient atrio ventricular block), and also incurs extra cost. Injection of contrast media, routinely performed to validate FFR guide wire placement, also induces hyperemia but to a lesser extent than adenosine 5,6 or other pharmacological agents. Contrast media injection can be an alternative method to measure FFR (cFFR), but the adequate method (contrast agent type and volume) to obtain cFFR value remains debated.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, adenosine can be contraindicated in some patients with asthma or severe chronic obstructive pulmonary disease (COPD), it can induce conductive complications (transient atrio ventricular block), and also incurs extra cost. Injection of contrast media, routinely performed to validate FFR guide wire placement, also induces hyperemia but to a lesser extent than adenosine 5,6 or other pharmacological agents. Contrast media injection can be an alternative method to measure FFR (cFFR), but the adequate method (contrast agent type and volume) to obtain cFFR value remains debated.…”
Section: Introductionmentioning
confidence: 99%
“…A small study reevaluating contrast FFR has found an improved correlation with FFR, as compared with what has been previously reported with resting indices, such as iFR and rest P d /P a . 39 To prove that contrast FFR more accurately predicts FFR and can be measured as easily as resting indices, a large, multicenter, international study is now underway and will compare the correlations between contrast FFR, iFR, and rest P d /P a to FFR in 750 patients (www.clinicaltrials.gov NCT02184117).…”
Section: Other Proposed Indexesmentioning
confidence: 99%
“…In order to facilitate FFR adoption, two different approaches have been proposed: intra coronary adenosine administration (13), and more recently introduction of contrast medium as an alternative hyperemic agent. Contrast medium induced FFR, studies have shown a good correlation between contrast induced Pd/Pa and adenosine mediated FFR (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 95%
“…Saline solution decreases coronary resistances and increases vasodilatation (11,12). Contrast media, on the other hand has already been evaluated as a hyperemic agent in FFR (14)(15)(16)(17). In one multicenter study, adjudicated by a central core laboratory, contrast mediated FFR compared favorably to adenosine mediated FFR and was superior to iFR for predicting CAS severity (15).…”
Section: Discussionmentioning
confidence: 99%